What is an Image? Roundtable transcription, International Visual Sociology Association annual conference, 16 September 2022. - Grady, John; Hansen, Susan; Rose, Gillian; Russworm, Treaandrea M.; Favero, Paolo; Toukan, Oraib; Abidin, Crystal; Lehner, Ace; Cambre, M.C.; David, Gaby; Rossetto, Tania (Visual Studies)
The article discusses the changing nature of images in the context of rapid technological advancements. Topics include the impact of technology on theory and practice, the potential for images to be used as tools of manipulation or social engagement and the challenges of defining and categorizing digital images.